2010
DOI: 10.1111/j.1467-9515.2010.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Active Labour Market Policy have an Impact on Social Marginalization?

Abstract: Countless evaluations of active labour market policy (ALMP) have been conducted in the last decade. The common denominator for most of these evaluations is a focus on employment (selfsufficiency) as the dependent variable, where the success of ALMP is measured in terms of the number of unemployed finding ordinary employment after (or immediately before) participating in an activation programme. The main argument in this article is that this focus is inadequate. For many long-term unemployed people, it would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 24 publications
3
29
0
1
Order By: Relevance
“…Most importantly, some of the ideal dependent variables were not available for this study. These include those used in previous studies of ALMPs and social capital, such as sense of social support and use of community resources (Creed et al 1998(Creed et al , 1999, perceptions of social isolation (Anderson 2009) and sense of social stigma (Breidahl and Clement 2010). Further, Anderson (2009) found that higher ALMP expenditure was associated with higher social capital amongst the unemployed.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Most importantly, some of the ideal dependent variables were not available for this study. These include those used in previous studies of ALMPs and social capital, such as sense of social support and use of community resources (Creed et al 1998(Creed et al , 1999, perceptions of social isolation (Anderson 2009) and sense of social stigma (Breidahl and Clement 2010). Further, Anderson (2009) found that higher ALMP expenditure was associated with higher social capital amongst the unemployed.…”
Section: Discussionmentioning
confidence: 84%
“…However, there is also evidence that ALMPs offer no added health and social benefits compared to open unemployment. In relation to the effect on well-being and physical health, no significant differences between the two groups were found in Sweden (Arnetz et al 1987;Westerlund et al 2001;Reine et al 2011), nor for social capital in Australia (Creed et al 1998) and Denmark (Breidahl and Clement 2010).…”
Section: The Health and Psychosocial Effects Of Unemployment And The mentioning
confidence: 85%
See 1 more Smart Citation
“…However, participants of work corporations have much more trust in their fellow citizens (in the neighbourhood), more trust in the municipality, more trust in people in general, and are intrinsically motivated to a higher extent than those who do not participate. This result, which resembles findings in the field of civic participation, is important since activation policies, and co-production in general, are expected to be beneficial in combating marginalization and fostering social cohesion (Anderson, 2009;Breidahl and Clement, 2010). If levels of trust are already high, this proposition would not be impossible, but difficult to become a reality.…”
Section: Conclusion and Discussionmentioning
confidence: 61%
“…UK spending on ALMP has actually fallen significantly since the mid-1980s, although this higher spending is largely explained by direct job creation in the public sector in this period, which has now been largely halted (Van Reenen 2004, 473). The UK's approach can be contrasted with high-spending countries such as Denmark and Sweden, who focus on, respectively, training programmes and employment subsidies -although both have increased the proportion of expenditure devoted to labour market services in recent years (see Berry 2014;Bonoli 2010;Cook 2008;Nielsen Breidhal and Clement 2010) -and other low-spenders such as Italy, which focuses its limited resources mainly on training. Germany and France have also moved closer to the UK's approach in recent years (Berry 2014;Heyes 2012;Vail 2008) -although clearly they retain significant investment in training -but the European country seemingly most similar to the UK is the Netherlands.…”
Section: What Is Almp?mentioning
confidence: 98%